The Effect of Laughter Therapy, a Low-Salt Diet, Exercise, and Physical Activity on Reducing Blood Pressure in Elderly Patients at the Sei Kepayang Timur Community Health Center, Asahan Regency - Rona RAngelin Purba; Sri Wahyuni Nasution; Wienaldi Wienaldi (CV. Inara, 2025)
Hypertension is a common health problem among the elderly and carries a risk of increasing cardiovascular complications. Non-pharmacological efforts such as laughter therapy, a low-salt diet, exercise, and physical activity are important strategies in controlling blood pressure. This study aims to analyze the effectiveness of laughter therapy, a low-salt diet, exercise, and physical activity on reducing blood pressure in elderly patients at the Sei Kepayang Timur Community Health Center in Asahan Regency. The study used a quasi-experimental design with a pre-test and post-test control group approach. The number of respondents was 60 elderly people who were divided equally into an intervention group of 30 people and a control group of 30 people. Data were analyzed using comparative statistical tests (paired t-test and chi-square test) with a significance level of p < 0.05. The results showed that in the intervention group, there was a decrease in mean systolic blood pressure from 150.2 mmHg to 135.4 mmHg, with a difference of 14.8 mmHg (p = 0.000), and a decrease in diastolic blood pressure from 93.2 mmHg to 84.4 mmHg, with a difference of 8.8 mmHg (p= 0.000). Other interventions, including a low-fat diet, exercise, and physical activity, were also shown to be effective in reducing both systolic and diastolic blood pressure. In conclusion, laughter therapy, a low-salt diet, exercise, and physical activity are effective in reducing blood pressure in the elderly. Based on these study results, the elderly are advised to regularly engage in laughter therapy, maintain a low-salt diet, and increase physical activity and exercise. Health institutions need to integrate this non-pharmacological intervention program into promotive and preventive services. Future research is expected to examine long-term effectiveness and expand the sample size.